The relationship between non-suicidal self-injury, identity conflict, and risky behavior among Druze adolescents - Toukhy, Nermin; Ophir, Shir; Stukalin, Yelena; Halabi, Samer; Hamdan, Sami (Frontiers in Psychiatry, 2022)
Objectives: This study aimed to explore the prevalence of non-suicidal self-injury (NSSI) among Druze adolescents in Israel, an ethnic minority, and examine the influence of identity conflict, depression, and performance of risky behaviors on such adolescents’ engagement in NSSI. This investigation is important because little is known about NSSI among adolescents from ethnic minorities. Methods: Overall, 290 Druze adolescents aged 16–18 (mean = 16.26, standard deviation = 0.9) years (63.9% female) participated in this study. They were recruited through snowball sampling from three Druze schools that agreed to participate in the study. All participants completed self-report measures for NSSI, depression, anxiety, engagement in risky behaviors, emotion regulation, sleep problems, and identity integration. Results: Almost 20% of the total sample engaged in NSSI. Those who engaged in NSSI reported more significant depression, anxiety, sleep problems, and engagement in risky behaviors when compared with those who did not engage in NSSI. Moreover, those who engaged in NSSI reported experiencing a higher level of identity conflict. Further analysis revealed an indirect effect of identity conflict on NSSI through engagement in risky behaviors. Conclusions: This study’s findings clarify the prevalence of NSSI among Druze adolescents, as well as contributing factors, and also highlights the importance of developing interventions that specifically target this unique ethnic group.